Feasibility and Safety of Drug-Coated Balloon-Only Angioplasty for De Novo Ostial Lesions of the Left Anterior Descending Artery: Two-Center Retrospective Study - Li, Chuang; Ding, Xuebo; Wang, Lefeng; Li, Kuibao; Yang, Xinchun; Liu, Liping; Xu, Li (Frontiers in Cardiovascular Medicine, 2022)
Introduction There is limited evidence regarding the effectiveness of drug-coated balloon (DCB) angioplasty in the percutaneous treatment of complex de novo ostial coronary lesions. This study primarily aimed to explore the feasibility and safety of this innovative approach for ostial lesions in the left anterior descending artery (LAD). Methods Patients treated with paclitaxel DCB or second-generation drug-eluting stents (DES) were retrospectively enrolled from two large centers. The primary endpoints were major adverse cardiovascular events (MACE), including cardiovascular death, target lesion revascularization (TLR), target vessel revascularization, and recurrent myocardial infarction related to target artery occlusion. Cox regression analysis was used to identify risk factors for MACE, and propensity score matching was performed to minimize selection bias. Results A total of 388 patients were included; among them, 52 were treated with paclitaxel DCB, and 336 with DES for ostial LAD lesions. Using propensity score matching, 49 patients were treated with DCB-only and 49 with the DES strategy. The average follow-up time was 12 months; subsequently, a non-significant decrease in MACE rate was observed in the DCB-only angioplasty treatment group (MACE: 6 vs. 6%, p = 1.0; TLR: 2 vs. 4%, p = 0.56). Cox regression analysis indicated that DCB-only angioplasty was not an independent risk factor for adverse events after adjusting for confounding risk factors (hazard ratio: 1.713, p = 0.43). Conclusion The use of the DCB-only approach is an innovative and optional strategy in the treatment of isolated ostial LAD disease. A further randomized trial is of necessity to confirm the feasibility and safety of drug-coated balloon-only angioplasty for LAD de novo ostial lesions.